2018
DOI: 10.5152/tjg.2017.17340
|View full text |Cite
|
Sign up to set email alerts
|

New treatment of the pancreatic cystic neoplasm: Endoscopic ultrasonography-guided radiofrequency ablation combined with lauromacrogol ablation

Abstract: Pancreatic cystic neoplasms (PCNs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, they also revealed similar rates (67%) using an ethanol-sparing comparator, indicating that this approach can provide equally high therapeutic results protecting from the ethanol-related adverse events [31]. RFA combined with lauromacrogol injection has also been assessed in isolated reports, resulting in cyst disappearance, and implying that this may be a promising approach worthy of further assessment [49].…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, they also revealed similar rates (67%) using an ethanol-sparing comparator, indicating that this approach can provide equally high therapeutic results protecting from the ethanol-related adverse events [31]. RFA combined with lauromacrogol injection has also been assessed in isolated reports, resulting in cyst disappearance, and implying that this may be a promising approach worthy of further assessment [49].…”
Section: Discussionmentioning
confidence: 77%
“…We are currently performing another study, in which lauromacrogol and RFA combined with lauromacrogol ablation are being compared. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…A case study performed RFA followed by lauromacrogol ablation reported complete resolution at 3-month follow-up. [ 79 ] Similar studies that combine of multiple ablative techniques should also be evaluated for PCL management.…”
Section: Discussionmentioning
confidence: 99%